Review of the united states fish and wildlife service’s 2017 endangered species act delisting rule for the greater yellowstone ecosystem grizzly bear - Shafer, Craig L. (Frontiers in Conservation Science, 2025)
The Greater Yellowstone Ecosystem grizzly bear (Ursus arctos horribilis) population and four other populations were listed as “threatened” in the lower 48 states by the US Fish and Wildlife Service (USFWS) on July 28, 1975, based on the 1973 Endangered Species Act (ESA). An agency Final Rule in the Federal Register, issued on March 29, 2007, made it a distinct population segment (DPS) and removed the GYE population from the ESA listing. After litigation, a federal District Court ordered relisting on September 2, 2009, and vacated the 2007 rule. The USFWS appealed the decision and lost. On March 16, 2016, the agency issued a Proposed Rule to again delist this grizzly bear population, and a 90-day public comment period followed. A review of the public comments and agency responses found in the Federal Register Final Rule of July 31, 2017, reveals that the public perceived that the agency did not always respond fairly or comprehensively to some of the pertinent bear policies. Some issues were overlooked, given inadequate treatment, and suffered from misinformation. These topics include habitat fragmentation, migration and dispersal, habitat connectivity, other population proximity, private land, and others. The 2017 rule also delisted the GYE grizzly bear. After the USFWS objected, a federal Circuit Court agreed with a lower District Court that the 2017 delisting rule be vacated and the GYE grizzly bear be relisted. A Federal Register notice issued on September 24, 2018, affirmed that action. On March 31, 2021, the agency changed its position and recommended continued listing of the GYE grizzly bear. Congress introduced legislation from 2023-2025 to delist the GYE and NCDE grizzly bear populations. Responding to State petitions to delist, the agency concluded on January 20, 2025, that the lower-48 grizzly bears should remain listed (USFWS 2025). Although the topic of the 2017 delisting rule is now eight years old, the extent to which the USFWS did not respond adequately to certain topics is informative and timely since the agency could be compelled to write more delisting rules and respond to more public comments in the future.